Personality is tightly coupled to vasopressin-oxytocin neuron activity in a gregarious finch - Kelly, Aubrey M.; Goodson, James L. (Frontiers in Behavioral Neuroscience, 2014)
Nonapeptides of the vasopressin-oxytocin family modulate social processes differentially in relation to sex, species, behavioral phenotype, and human personality. However, the mechanistic bases for these differences are not well understood, in part because multidimensional personality structures remain to be described for common laboratory animals. Based upon principal components (PC) analysis of extensive behavioral measures in social and nonsocial contexts, we now describe three complex dimensions of phenotype ("personality") for the zebra finch, a species that exhibits a human-like social organization that is based upon biparental nuclear families embedded within larger social groups. These dimensions can be characterized as Social competence/dominance, Gregariousness, and Anxiety. We further demonstrate that the phasic Fos response of nonapeptide neurons in the paraventricular nucleus of the hypothalamus and medial bed nucleus of the stria terminalis are significantly predicted by personality, sex, social context, and their interactions. Furthermore the behavioral PCs are each associated with a distinct suite of neural PCs that incorporate both peptide cell numbers and their phasic Fos responses, indicating that personality is reflected in complex patterns of neuromodulation arising from multiple peptide cell groups. These findings provide novel insights into the mechanisms underlying sex- and phenotype-specific modulation of behavior, and should be broadly relevant, given that vasopressin-oxytocin systems are strongly conserved across vertebrates.